Corporate governance mechanism constraining Earning Management in Malaysian listed companies - Khan, M.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper proposes to investigate the postulations of renowned agency theory and Earning Management (EM) in relation to Corporate Governance (CG) mechanism and external audit that CG mechanism and external auditor constrains EM. The paper conceptualized three attributes (board size, audit committee financial expertise and industry specialized auditor) from CG mechanism and external auditor in relation to EM practices in Malaysian listed companies. This is a conceptual paper which proposes to investigate the correlation between the size of board and EM, financial expertise of audit committee and EM and industry specialized auditor and EM. The proposed study has value for Malaysian government, policy makers, corporate boards, stock exchange and shareholders by highlighting the distinct impact of EM practices and its relation with board size, audit committee financial expertise and industry specialized auditor. Â© 2015 IEEE.